2020
DOI: 10.1101/2020.11.15.20231985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of functional capacity with cardiopulmonary exercise testing in non-severe COVID-19 patients at three months follow-up

Abstract: IntroductionLong-term effects of Coronavirus Disease of 2019 (COVID-19) and their sustainability in a large number of patients are of the utmost relevance. We aimed to determine: 1)functional capacity of non-severe COVID-19 survivors by cardiopulmonary exercise testing (CPET); 2)those characteristics associated with worse CPET performance.MethodsWe prospectively enrolled the first 150 consecutive subjects with laboratory-confirmed COVID-19 infection discharged alive from March to April 2020 at Azienda Sanitari… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 17 publications
3
40
1
5
Order By: Relevance
“…In the context of the COVID-19 aftermath, somewhat similar findings were found in a study by Clavario et al, [19] where 34.5% of the COVID-19-affected participants (non-athletes) had below VO 2max values, whereas 65.5% had above the 85% predicted value, which is indicative of normal values. Furthermore, pulmonary function test parameters were within the normal limits.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the context of the COVID-19 aftermath, somewhat similar findings were found in a study by Clavario et al, [19] where 34.5% of the COVID-19-affected participants (non-athletes) had below VO 2max values, whereas 65.5% had above the 85% predicted value, which is indicative of normal values. Furthermore, pulmonary function test parameters were within the normal limits.…”
Section: Discussionsupporting
confidence: 85%
“…Ever since the coronavirus disease 2019 (COVID- 19) outbreak emerged at the end of 2019 in a multimillion city in central China, patterns of our daily life have been dramatically changed [1]. In the absence of an effective medication or vaccine, the World Health Organization and various governments around the world have emphasized personal efforts such as temporary lockdown, social distancing, face mask wearing, increased hand hygiene, etc., to minimalize the risk of viral spread [2].…”
Section: Introductionmentioning
confidence: 99%
“…This approach was used in the SARS-CoV-1 pandemic and revealed that whilst exercise tolerance was impaired in 57% of patients, a disconnect was often evident between individuals with impaired diffusion capacity, such that those with impaired peak oxygen uptake on CPET were not always the same group of individuals with impaired gas exchange [ 10 ]. In the SARS-CoV-2 pandemic, Clavario et al [ 7 ] utilised CPET in 110 patients (age: 61.7 ± 8 years) and reported impaired aerobic capacity (defined as a peak oxygen consumption of <85% predicted) in 34% of non-severe (defined as those that did not require ITU) patients three months after discharge which was attributed predominantly to muscular impairment. Similarly, one month following discharge, patients demonstrated impaired aerobic capacity which was not explained by pulmonary function changes, but likely attributable to physical deconditioning [ 20 ] and 70% of patients were limited by decreases in peripheral muscle mass [ 21 ].…”
Section: Functional and Exercise Capacity Following Covid-19mentioning
confidence: 99%
“…There is also increasing recognition that between 30- 60% of individuals report protracted symptoms, such as fatigue and dyspnoea, following resolution of their acute illness [ 5 •• , 6 •• ]; variably termed the ‘long-COVID’ or the post-COVID syndrome. Exertional dyspnoea and exercise intolerance are prominent clinical features reported in this syndrome [ 7 , 8 ] and there is increasing interest in how best to objectively characterise and followed-up this issue with objective tests. Similar concerns were apparent following the first SARS pandemic with SARS-CoV-1 infection, in 2003.…”
Section: Introductionmentioning
confidence: 99%
“…The CPET should be performed in situations of medical control, with exhaustive monitoring [ 80 , 81 , 82 ], considered the gold standard [ 83 ], and allows the detection of problems that should be assessed by a specialist. Although it could be too demanding, the 6MWT is an optimal alternative to use, both the CPET and 6MWT are already used in COVID-19 patients [ 84 , 85 ]. When an impairment is found, cardiovascular exercise of moderate intensity [ 32 ], with control of SpO 2 (to stop if values decrease by <90% or a decrease by more than 4% from baseline [ 86 ]) and rate of perceived exertion in the Borg scale between 3 and 5 [ 87 ], is recommended for optimal outcome and safety [ 32 ].…”
Section: Discussionmentioning
confidence: 99%